Examining the Causal Nexus between Foreign Direct Investment and Economic Growth in The Gambia - Yahya Njie; Ebou Correa (Universitas Airlangga, 2026)
Objective: Foreign Direct Investment acts as a significant factor in enhancing the macroeconomic performance of host countries, especially those that are less developed or in transition. Thus, understanding the causal association between foreign direct investment and economic growth in The Gambia is important for shaping policies that promote sustainable development. This study examines the causal relationship between foreign direct investment and economic growth in The Gambia. Method: This study utilised annual time series data from 1970 to 2022, using the Vector Error Correction Model (VECM) in examining the causal relationship between Foreign Direct Investment and Economic Growth in The Gambia. Findings: The results show a significant causal relationship between Foreign Direct Investment and economic growth. Originality/Value: Prior studies show mixed results on the relationship between Foreign Direct Investment and GDP across countries. This study focuses on The Gambia to clarify the direction of causality and fill this gap. It contributes to the literature by applying the VECM model, which effectively handles non-stationary time series data and captures long-run relationships among cointegrated variables, providing useful insights for policymakers to promote growth and attract FDI. Practical/policy implication: The study recommends policymakers prioritize creating a business-friendly environment to attract more foreign direct investment. This could include offering incentives such as tax breaks, reducing regulatory barriers, and ensuring political stability to instill investor confidence.